PENGARUH OBAT BUPIVACAIN TERHADAP MAP DAN FREKUENSI NADI PADA ANESTESI SPINAL DI RS PKU MUHAMMADIYAH GOMBONG - Catur Nugroho Kuncoro Jati; Marta Tania Gabriel Ching Cing; Endiyono; Rully Annisa (Jurnal Riset Multidisiplin Edukasi, 2026)
Background: Hemodynamic changes are common during spinal anesthesia, particularly following the administration of bupivacaine, which may affect mean arterial pressure (MAP) and heart rate. Monitoring these parameters is essential to maintain hemodynamic stability throughout surgical procedures. Objective: This study aimed to determine the effect of bupivacaine administration on mean arterial pressure (MAP) and heart rate in patients undergoing spinal anesthesia at PKU Muhammadiyah Gombong Hospital. Methods: This quantitative study employed a pre-experimental one-group pretest-posttest design. A total of 181 respondents were recruited using accidental sampling. Mean arterial pressure and heart rate were measured 5 minutes before and 5 minutes after the administration of spinal anesthesia. Data were analyzed using the Wilcoxon Signed-Rank Test. Results: A significant change in mean arterial pressure was observed following bupivacaine administration (p < 0.001). In contrast, no significant change was found in heart rate (p = 0.823). Conclusion: Bupivacaine administration significantly affected mean arterial pressure but did not significantly influence heart rate in patients undergoing spinal anesthesia.